Cultural effects on the transmission rate of COVID-19 - Su, Ziling (Nanyang Technological University, 2021)
This paper seeks to combine various important cultural factors and identify the most significant cultural determinant in affecting the rate of COVID-19 transmission. Studies have supported that cultural differences play a pivotal role in accounting for the variation of COVID-19 transmission across countries. However, existing literature only focused on a single cultural determinant to explain its effects on the transmission outcome of COVID-19. Despite culture being a multidimensional construct, no previous studies have attempted to combine various cultural factors to identify the most pervasive factor in affecting COVID-19 transmission. Hence, our study attempts to bridge this research gap by including 4 main cultural determinants: individualism-collectivism, importance of religion, importance of family ties and social trust. Using Hofstede's individualism index and data from the World Value Survey to measure the scores of the mentioned cultural factors in approximately 102 countries, our empirical evidence suggests that the individualism-collectivism dimension is the most significant factor which influences the transmission rate of COVID-19. Our results remain statistically significant after conducting a series of robustness checks.